2020
DOI: 10.1177/1120672120929959
|View full text |Cite
|
Sign up to set email alerts
|

Orbital plasmacytoma as the presenting feature in multiple myeloma

Abstract: A 50-year-old female patient presented with protrusion of the left eye for 1 month. Examination showed abaxial proptosis, restriction of extraocular movements, and elevated intraocular pressure. Computed tomography of the orbits showed soft tissue enhancing lesion in the superolateral aspect of the left orbit with lytic lesions in calvarium. Fine needle aspiration cytology of the lesion revealed a diagnosis of plasmacytoma with positive CD138 and CD38 immunohistochemical stains. Erythrocyte sedimentation rate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
6
0
2
Order By: Relevance
“…Four of the sixteen cases in our study were diagnosed with DLBCL constituting the second most prevalent NHL type. This concurs with the survey of Roositalab and Rastogi et al 12 , 14 The other possibility when there are sheets of mature plasma cells with clonality being expressed on ICC suggests a solitary plasmacytoma in the absence of marrow involvement 15 . In our study, there was one case of solitary plasmacytoma.…”
Section: Discussionsupporting
confidence: 93%
“…Four of the sixteen cases in our study were diagnosed with DLBCL constituting the second most prevalent NHL type. This concurs with the survey of Roositalab and Rastogi et al 12 , 14 The other possibility when there are sheets of mature plasma cells with clonality being expressed on ICC suggests a solitary plasmacytoma in the absence of marrow involvement 15 . In our study, there was one case of solitary plasmacytoma.…”
Section: Discussionsupporting
confidence: 93%
“…Der Wirkmechanismus liegt einerseits in der Inhibition der Phospholipase A2 und der Zyklooxygenase sowie andererseits in einem immunsuppressiven Effekt [ 12 ]. In den wenigen beschriebenen Fallberichten wird von spontanen Rückbildungen [ 7 ], einer Kombinationstherapie von Steroiden und Chemotherapie [ 3 , 13 ] sowie gar einem akuten operativen Vorgehen mittels lateraler Kanthotomie und Kantholyse berichtet [ 6 ].…”
Section: Diskussionunclassified
“…Dazu gehören eine Sinusvenenthrombose, eine orbitale Zellulitis sowie auch orbitale oder zerebrale Raumforderungen. Pathologische Parameter, wie erhöhte Blutkörperchensenkung, CRP-Erhöhung sowie LDH-Erhöhung sind im Zusammenhang mit dem multiplen Myelom bereits beschrieben [ 13 ]. Letztlich führten klonale λ‑Leichtketten zur Diagnose des multiplen Myeloms.…”
Section: Diskussionunclassified
“…Literature review identified a total of 111 previously reported cases in 68 articles regarding orbital involvement in patients with systemic MM (Table 2). 4,6-61…”
Section: Resultsmentioning
confidence: 99%